The Financial Times guide to making the right investment decisions : how to analyse companies and value shares - Cahill, Michael, 1962- (Financial times guides., 2012)
Michael Cahill is an established analyst and coach, and head of MarketMatters, a training company that specialises in demystifying company valuation and how markets work. A Cambridge economics graduate, he worked for 16 years as an investment analyst in both broking and fund management, including 10 years at UBS Warburg as a member of one its top-rated research teams. Michael’s clear and common sense approach to analysing companies and valuing shares was first published in 2003. In this edition, he has taken this subject a stage further, creating a new framework that makes company valuation even more intuitive and accessible. Michael’s energy and enthusiasm transforms the subject and inspires people to think about valuation and financial markets differently, prompting one course participant to comment: 'A fantastic teacher – helpful, resourceful, covered all the ground in great detail but made it all very real and really understandable’. Michael lives in London and as well as working in the UK he regularly teaches and coaches overseas.